The Effect of Various Milling Time Duration On The Characteristic of Glass Ionomer Cement (GIC) with The Addition of Liquid Pmve-Ma - Rudyardjo, Djony Izak; Ady, Jan; Fauzi, Aditya Budi (Indonesian Applied Physics Letters, 2020)
A study entitled The Effect of Milling Time Duration on the Characteristics of Glass Ionomer Cement (GIC) Dental Cement with the Addition of Liquid PMVE-MA aims to determine the effect of milling time duration on the physical and mechanical properties of Glass Ionomer Cement, and to determine the optimum milling time duration in order to obtain GIC dental cement with the best characteristic to be applied as a dental restoration material. The duration of the milling time was 80 minutes, 90 minutes, 100 minutes, and 110 minutes. After the milling process, the next process was sintered at a temperature of 1200 for 1 hour to form Powder Glass Ionomer. Then Powder Glass Ionomer was added with Poly Methyl Vinyl Ether-Maleic Acid (PMVE-MA) to form a paste. The mixed paste was then formed. Sample characterization was the density test, the compressive strength test, and the vickers hardness test. The results of the density test obtained the highest value of 1.683 gram / cm3, the compressive strength test of 71.841 MPa, and the highest value of the hardness test of 92.3 Kg / mm2. These results increased as the increasing milling time duration up to 110 minutes.